The United States and mediation strategies in the Egyptian-Israeli peace process, 1973-1975 - Wesolowska, Ksenia (2017)
This thesis explores the US mediation strategies applied during the management of the Egyptian-Israeli dispute in the period of 1973-1975. More specifically, it focuses on the crucial US role in bringing Egypt and Israel towards a settlement from the 1973 October War to the brink of the Camp David settlement, realised under President Jimmy Carter. The centrepiece of the thesis is the mediation efforts during the Republican Presidencies of Richard Nixon (1969-74) and Gerald Ford (1974-77). This thesis examines how diverse contextual variables change and interact with the mediator’s methods of sequencing and packaging of the issues in conflict management. The key analysis emerges from Secretary of State Henry Kissinger’s mediation, especially by looking at his ‘concession-hunting’ procedure and its accompanying ‘hard bargaining’ tactics after the 1973 October War. The analysis incorporates specific case studies of Kissinger’s mediation efforts, which led to the signature of the Sinai I and Sinai II disengagement agreements, but also resulted in the reassessment of the US foreign policy towards Israel in March 1975. In this thesis it will be seen that concession-hunting processes differed in their processes and outcomes This thesis concludes that in a protracted conflict, the concession-hunting is a method preferable for bridging the gap between the disputants, as compared to the holistic approach. If performed by a mediator with concrete ‘powers’, it extracts concessions in a gradual manner and allows for third party implementation of various methods to ‘soften up’ the hard negotiating positions of the disputants.